Translating local wisdom into visual identity: an ADDIE-based framework for logo design in Brumbung Village - Masnuna Masnuna; Rijal Jadhuk Firmansyah (Gelar: Jurnal Seni Budaya, 2026)
This study addresses the limited research on how local wisdom can be systematically translated into rural visual identity systems. It aims to identify the local wisdom values of Brumbung Village and articulate them into a logo-based visual identity. The novelty lies in adapting the ADDIE framework as a cultural-interpretive design model for transforming historical, social, and agrarian values into visual communication elements. Using a qualitative design-based approach, data were collected through semi-structured interviews, participant observation, documentation, and validation sessions with village officials, cultural experts, and community representatives. Data were analyzed through thematic coding, symbolic interpretation, and visual translation. The resulting logo integrates symbols of protection, continuity, water, and community solidarity. Evaluation with 44 respondents indicates that the logo is perceived as culturally relevant and representative of Brumbung Village. This study contributes to visual identity, visual semiotics, and place identity research by offering a systematic framework for translating local wisdom into visual communication.